How Civil Society Organisations Changed the Regulation of Clinical Trials in India - Salla Sariola; Roger Jeffery; Amar Jesani; Gerard Porter (Routledge, 2022)
In 2005 India changed its pharmaceutical and innovation policy that facilitated a dramatic increase in international clinical trials involving study sites in India. This policy shift was surrounded by controversies; civil society organisations (CSOs) criticised the Indian government for promoting the commercialisation of pharmaceutical research and development. Health social movements in India fought for social justice through collective action, and engaged in normative reasoning of the benefits, burdens and equality of research. They lobbied to protect trial participants from structural violence that occurred especially in the first 5–6 years of the new policy. CSOs played a major role in the introduction of new regulations in 2013, which accelerated a decline in the number of global trials carried out in India. This activism applied interpretations of global social justice as key ideas in mobilisation, eventually helping to institutionalise stricter ethical regulation on a national level. Like government and industry, activists believed in randomised controlled trials and comparison as key methods for scientific knowledge production. However, they had significant concerns about the global hierarchies of commercial pharmaceutical research, and their impact on the rights of participants and on benefits for India overall. Pointing to ethical malpractices and lobbying for stricter ethical regulations, they aimed to ensure justice for research participants, and developed effective strategies to increase controls over the business side of clinical research.